Fort At Lio Mato And The Life Of Government, Brunei Connections And Brooke Histories - Valerie, Mashman (Pustaka Negeri Sarawak, 2021)
This paper takes the history of the Fort at Lio Mato, recorded as being built in 1911 during the time of Brooke Resident R.S. Douglas and events leading to its institution, through the voice of a Kelabit oral history. According to the Kelabit oral history, "the life of government," ulunperitah began in the time of Brunei rule in the Baram and continued with the establishment of the Fort at Lio Mato, opening of new routes for trade and new alliances gained by peacemaking. This oral history provides an opening to discuss two points: the perception of "the life of government" having its origins in the time of Brunei rule, the role of local people in the making of the fort. This shifts the historical emphasis away from Brooke records to a layered history at the frontier of the Ba ram district, which was the geographic and economic hinterland of Brunei before cession to the Brooke administration in 1882. This is a history not determined by territorial boundaries, but it is gleaned through people who moved freely across vast tracts of north-eastern Borneo.